Troponin-I concentration 72 h after myocardial infarction correlates with infarct size and presence of microvascular obstruction. Issue 12 (31st May 2007) - Younger, John F; Plein, Sven; Barth, Julian; Ridgway, John P; Ball, Stephen G; Greenwood, John P
Abstract : Objectives: The aim of this study was to use late gadolinium hyper-enhancement cardiac magnetic resonance (LGE-CMR) imaging to determine if a 72-h troponin-I measurement would provide a more accurate estimation of infarct size and microvascular obstruction (MVO) than serial creatine kinase (CK) or early troponin-I values. Methods: LGE-CMR was performed 3.7±1.4 days after medical treatment for acute ST elevation or non-ST elevation myocardial infarction. Infarct size and MVO were measured and correlated with serum troponin-I concentrations, which were sampled 12 h and 72 h after admission, in addition to serial CK levels. Results: Ninety-three patients, of whom 71 had received thrombolysis for ST elevation myocardial infarction, completed the CMR study. Peak CK, 12-h troponin-I, and 72-h troponin-I were related to infarct size by LGE-CMR (r = 0.75, p<0.0001; r = 0.56, p = 0.0003; r = 0.62, p<0.0001 respectively). Serum biomarkers demonstrated higher values in the group with MVO compared with those without MVO (Peak CK 3085±1531 vs 1471±1135, p<0.001; 12-h troponin-I 58.3±46.9 vs 33.4±40.0, p = 0.13; 72-h troponin-I 11.5±9.9 vs 5.5±4.6, p<0.005). The correlation between the extent of MVO and 12-h troponin-I was not significant (r = 0.16), in contrast to the other serum biomarkers (peak CK r = 0.44, p<0.0001; 72-h troponin-I r = 0.46, p = 0.0002). Conclusion: A single measurement of 72-h troponin-I is similar to serial CK measurements in the estimation of both myocardial infarct size and extent of MVO, and is superior to 12-h troponin-I measurements.